The Spalding Family of Maryland, Kentucky and Georgia from 1658-1963 - Spalding, Hughes (Stein Printing Company Atlanta, Georgia, 1963)
History of How the Pioneer Catholic Spalding in America Originated in Maryland and Spread to Kentucky, Georgia, and Other States
Donated by Edwin W. Beitzell